Legality and Limits of Authority of Notaries Who Also Serve as Class II Auction Officials in the Settlement of Auction Disputes - Ferri Ardiansyah, Muhammad (JUSTISI, 2026)
This study aims to examine the authority of notaries who also serve as Class II Auctioneers in the implementation of auctions in Indonesia, focusing on two main aspects, namely the auction implementation procedures based on Indonesian positive law and the role and responsibilities of notaries in handling disputes that arise during the auction process. The method used in this study are normative law with a legislative and conceptual approach sourced from legislation, legal literature, and expert opinions. The novelty of this research lies in its comprehensive analysis of the application of the dual authority of notaries in the context of auction implementation and the integration of the general principles of good governance (AUPB) as ethical and juridical principles in the auction process. The results of the study show that the implementation of auctions by Class II Auctioneers must follow strict procedures, including auction announcements, participant registration, explanation of auction objects, price bidding, and determination of winners, all of which must be documented in a transparent and accountable manner. Specific findings of the study reveal that the dual authority of notaries creates a unique complexity of responsibilities. In handling disputes, notaries/auction officials not only act as transaction executors but also as quasi-judicial decision-makers at certain stages. In this case, the application of AUPB plays an important role as a guideline in the use of discretion to remain in line with legal regulations, produce fair decisions, and encourage clean, professional, and trustworthy government administration. The conclusion of this study is that the integration of AUPB in every stage of the auction is a key strategy to mitigate potential disputes and conflicts of interest inherent in this dual authority. The implication is that separate ethical and procedural guidelines are needed for notaries who also serve as Auction Officials to ensure consistency and fairness.